THE ROLE OF POSYANDU CADRES IN PREVENTING STUNTING IN CHILDREN AGED 0-59 MONTHS - Saputri, Anggraini; Widiawati, Susi; Wirahandayani, Marthalisa (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This research is to determine the role of posyandu cadres in preventing stunting in children 0-59 months. Method: This research is quantitative research with a descriptive design. The sample was 70 parents who had children aged 0-59 months.  Samples were taken using purposive sampling. Data collection was carried out from 10 September to 10 October 2025. The instrument used was a questionnaire on the characteristics and roles of posyandu cadres, and the data was analyzed univariately. Result: The majority of 65 (92.9%) respondents stated that the role of cadres in monitoring children's growth and development was good. 50 (71.4%) respondents stated that cadres provided education to parents. 46 (65.7%) respondents stated that cadres monitored breastfeeding and MP-ASI well. 46 (65.7%) respondents stated that cadres monitored the health of pregnant and postpartum women well. Conclusion: The role of posyandu cadres is mostly good in preventing stunting in children aged 0-59 months. It is necessary to maintain and increase the role of posyandu cadres in preventing stunting cases in children under five.